Simbol Gunung dan Air pada Lanskap Budaya Situs Candi Agung di Kalimantan Selatan - Imam Hindarto; Vida Pervaya Rusianti Kusmartono; Wahyu (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
The Candi Agung site is one of the cultural landscapes in South Kalimantan. The value of this cultural landscape is closely related to living traditions, belief systems, art and literature. This cultural landscape also represents the symbols of mountains and water in the culture of the Banjar people. These two physical-naturalistic components not only describe the landscape of South Kalimantan which consists of the Meratus Mountains and the Barito River but also describe the cultural landscape of the people who inhabited it. This study discusses the meaning of mountains and water in the cultural landscape of the Candi Agung Site. The aim is to understand the Candi Agung Site as an associative cultural landscape in Banjar culture. In order to understand this, data collection was carried out through observations of the Candi Agung Site and the views of the surrounding community. A documentation study on the Lambung Mangkurat Museum collection was carried out to complete the observation data. The analysis was carried out by describing aspects of mountain and water symbolism in the Lambu Mangkurat Story and the Banjar Kings Dynasty and Waringin City or known as the Banjar Hikayat. Apart from that, descriptions were also made of literary works entitled Tutur Candi. The interpretive framework of this study refers to the view that culture is a symbol system. This study produces an understanding of the cultural system of the Banjar people which was represented in the myth of the sacredness of mountains and water. These two natural elements are representations of supernatural forces which were manifested in the toponymy "mountain" of Candi Agung and the anthroponymy of Tunjung Buih. The connection between the two also represents harmony between the microcosm and the macrocosm.   Key words: Environment, cultural landscape, microcosm, dualism